2002
DOI: 10.1074/jbc.m200301200
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopically and Kinetically Distinct Conformational Populations of Sol-Gel-encapsulated Carbonmonoxy Myoglobin

Abstract: We have used sol-gel encapsulation protocols to trap kinetically and spectroscopically distinct conformational populations of native horse carbonmonoxy myoglobin. The method allows for direct comparison of functional and spectroscopic properties of equilibrium and non-equilibrium populations under the same temperature and viscosity conditions. The results implicate tertiary structure changes that include the proximal heme environment in the mechanism for population-specific differences in the observed rebindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(111 citation statements)
references
References 112 publications
3
108
0
Order By: Relevance
“…The present treatment represents a distillation and out growth of our recent work utilizing sol-gel encapsulation and glassy matrices to modulate protein dynamics in a way that provides a direct bridge between cryogenic and ambient domains Dantsker et al, 2005a;Dantsker et al, 2005b). We (Khan et al, 2000;Dantsker et al, 2002;Samuni et al, 2002;Dantsker et al, 2005a;Dantsker et al, 2005b) and others (Sottini et al, 2004;Sottini et al, 2005a;Sottini et al, 2005b;Sottini et al, 2005c) have shown that this approach of using high viscosity solvents and matrices exposes the dynamical events that give rise to the solution phase functional properties observed in solution at ambient temperatures. …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The present treatment represents a distillation and out growth of our recent work utilizing sol-gel encapsulation and glassy matrices to modulate protein dynamics in a way that provides a direct bridge between cryogenic and ambient domains Dantsker et al, 2005a;Dantsker et al, 2005b). We (Khan et al, 2000;Dantsker et al, 2002;Samuni et al, 2002;Dantsker et al, 2005a;Dantsker et al, 2005b) and others (Sottini et al, 2004;Sottini et al, 2005a;Sottini et al, 2005b;Sottini et al, 2005c) have shown that this approach of using high viscosity solvents and matrices exposes the dynamical events that give rise to the solution phase functional properties observed in solution at ambient temperatures. …”
mentioning
confidence: 93%
“…These would include for Mb, the dynamics contributing to the relaxation of the initial photoproduct tertiary structure back to the equilibrium deoxy conformation and for hemoglobins the additional larger scale motions required for changes in quaternary structure. Both categories of dynamics can be greatly slowed within sol-gel matrices relative to the operative time scales of the C and D tiers of dynamics (Bettati and Mozarrelli, 1997;Das et al, 1999;Khan et al, 2000;Abbruzzetti et al, 2001;Dantsker et al, 2002;Samuni et al, 2002;Shibayama and Saigo, 2003;Samuni et al, 2004;Viappiani et al, 2004). Consequently, the above A, B, C and D scheme can be explored within the conformational boundaries of different trapped tertiary and quaternary structures that represent both equilibrium and nonequilibrium conformational distributions.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] In addition, tertiary and quaternary conformational changes in heme proteins, such as myoglobin (Mb) and hemoglobin (Hb), can be inhibited or dramatically slowed, which allows these proteins to be "trapped" and studied in non-equilibrium structural conformations. [14][15][16][17][18][19][20][21][22] The origin of the stability imparted by the silica sol-gel matrix is complex. Since the mean pore diameters in aged wet sol-gels (typically <10 nm) are comparable to the diameters of Mb and Hb, the pore walls could physically restrict protein motions.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility provided by silica gel encapsulation to reduce the rate of conformational changes by orders of magnitude, increasing the kinetic separation of tertiary and quaternary relaxations [57,58,[80][81][82][83][84][85][86][87][88][89][90][91][92], has been extensively exploited by several groups to make accessible to spectroscopic investigation species that are normally poorly populated, or metastable on the time scale of solution experiments. Not surprisingly, many of these studies concern hemoglobin (Hb), myoglobin and other heme binding proteins, since the availability of a sensitive, intrinsic chromophoric signal allowed to achieve an unprecedented level of detail in the comprehension of structure-dynamic-function relationships.…”
Section: Heme Proteinsmentioning
confidence: 99%
“…Since the quaternary structural change of encapsulated Hb is greatly slowed down, tertiary intermediate states along the R T transition could be observed by conventional spectroscopic methods such as UV resonance Raman spectroscopy [86,89,90]. In particular, it has been shown that after photolysis of HbCO encapsulated in the T state, both the E and F helices assume intermediate positions with respect to those that characterize the Hb equilibrium states.…”
Section: Trapping Reaction Intermediates: Inhibition Of Conformationamentioning
confidence: 99%